2016
DOI: 10.1186/s12889-016-3686-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmaceutical, illicit drug, alcohol, nicotine and caffeine levels in wastewater with sale, seizure and consumption data for 8 European cities

Abstract: BackgroundMonitoring the scale of pharmaceuticals, illicit and licit drugs consumption is important to assess the needs of law enforcement and public health, and provides more information about the different trends within different countries. Community drug use patterns are usually described by national surveys, sales and seizure data. Wastewater-based epidemiology (WBE) has been shown to be a reliable approach complementing such surveys.MethodThis study aims to compare and correlate the consumption estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 48 publications
(73 reference statements)
4
82
1
6
Order By: Relevance
“…The potential rapid degradation of EtS and EtG, especially EtG (Figures a and b), in the sewer system may limit their applicability as biomarkers for the estimation of alcohol consumption in the population, although both of them are still currently used in urinalysis to detect alcohol consumption in individuals . With a complete loss after only 2 hours in both RM and GS reactors, EtG is not recommended to be used to estimate alcohol consumption in WBE studies, which supports the practice in all WBE studies related to alcohol after the initial assessment of Reid et al (Table ). In general, as found in this and other studies, glucuronide compounds are very quickly transformed in wastewater, and hence are not suitable to be used as biomarkers in WBE.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The potential rapid degradation of EtS and EtG, especially EtG (Figures a and b), in the sewer system may limit their applicability as biomarkers for the estimation of alcohol consumption in the population, although both of them are still currently used in urinalysis to detect alcohol consumption in individuals . With a complete loss after only 2 hours in both RM and GS reactors, EtG is not recommended to be used to estimate alcohol consumption in WBE studies, which supports the practice in all WBE studies related to alcohol after the initial assessment of Reid et al (Table ). In general, as found in this and other studies, glucuronide compounds are very quickly transformed in wastewater, and hence are not suitable to be used as biomarkers in WBE.…”
Section: Discussionmentioning
confidence: 87%
“…Cot satisfies this set of 4 criteria to be used for population estimation purpose while HCot does not meet the average 10% loss threshold. The caveat for Cot here is that it should not be used as a single population marker as there are differences in tobacco consumption among regions or countries . Moreover, a recent study by Tscharke et al also suggested to monitor two alkaloids – anabasine and anatabine – which are specific to dried tobacco in addition to nicotine and cotinine to obtain a better picture of the tobacco consumption situation.…”
Section: Discussionmentioning
confidence: 99%
“…In WBE studies, tobacco use can be estimated by the analysis of two urinary metabolites of nicotine; cotinine and trans-3′-hydroxycotinine3233343536. While enzymatic deconjugation is necessary to quantify total cotinine in wastewater, there has been no significant difference observed between measurements made with and without the enzyme treatment for trans-3′-hydroxycotinine32.…”
mentioning
confidence: 99%
“…Other studies that have used a multi-indicator approach [12][13][14][15][16][17][18][19][20] have also found a general agreement between trends in drug target residues in wastewater and trends in other indicators of drug consumption. Our study was conducted over a much longer time-frame and accounts for multiple sources of uncertainty, such as the concentration measurements, the daily flow estimates and the estimated population sizes, through our Bayesian hierarchical regression model.…”
Section: Comparison With Other Evidencementioning
confidence: 68%
“…No single measure can provide a full picture of regional drug use and current trends [10,11]. A multi-indicator approach is required, incorporating commensurate data such as population surveys and police data [12][13][14][15][16][17][18][19][20]. Several of the previous comparisons of wastewater data with other indicators of drug consumption have been limited by the single week of sampling issue.…”
Section: Introductionmentioning
confidence: 99%